Evaluation of arterial stiffness and subclinical atherosclerosis in patients with Behçet's disease without cardiovascular involvement - Alp Yıldırım; Mustafa Serkan Karakaş; Ali Yaşar Kılınç; Refik Emre Altekin; Ali Selim Yalçınkaya (KARE Publishing, 2016)
Objective: This study was conducted to evaluate arterial structure and function with assessment of pulse wave velocity (PWV) and carotid intima-media thickness (CIMT) in patients with Behçet's disease (BD).  Methods: Thirty patients (13 female, 17 male) with BD and 30 age, sex-matched healthy controls (12 female, 18 male) with no known cardiovascular disease were enrolled in this study. Carotid-femoral PWV and CIMT were measured.  Results: PWV was higher in BD patients compared with control group (6.35+-1.05 vs. 5.75+-0.83, respectively; p=0.017). There was no significant difference in maximum CIMT (0.751+-0.077 mm vs. 0.735+-0.079 mm, respectively; p=0.435), or mean CIMT (0.643+-0.070 mm vs. 0.629+-0.069, respectively; p=0.452). Maximum CIMT, mean CIMT, and PWV were positively correlated with duration of disease (r=0.410, p=0.025; r=0.404, p=0.027; and r=0.362, p=0.049, respectively).  Conclusion: Findings suggest that endothelial function is impaired in cases of BD before visible structural changes to arterial wall. PWV is more useful measurement than CIMT in determination of vascular damage in BD, especially in early stage of disease duration.